A MODEST RESPONSE TO EMPIRICAL SKEPTICISM ABOUT INTUITIONS. (9th September 2014) - Osborne, Philip
Abstract In his paper entitled "How to Challenge Intuitions Empirically Without Risking Skepticism, " Jonathan Weinberg challenges the practice of using intuitions to substantiate philosophical theses by appealing to the principle (defended empirically) that we ought to trust only evidence sources that are not "hopeless, " where an evidence source is hopeless when it exhibits "fallibility unmitigated by a decent capacity for detecting and correcting the errors it entails." Since intuitions are hopeless, they ought not be trusted. I respond by appealing to an alternative principle and defend this alternative by arguing that it explains data regarding the conduct of many our epistemic practices better than Weinberg's principle of hopefulness.